Cal Tjader the life and recordings of the man who revolutionized Latin jazz - Reid, S. Duncan 1961- (McFarland, 2013)
"The extensive research going into this book features many interviews with family, friends and colleagues both in the Bay Area and elsewhere; all the liner notes throughout Tjader's prolific recorded output; and interviews with the man himself as well as relevant articles and books. An exhaustive discography chronicles all his sessions"..